Proceedings of the Canadian society of allergy and clinical immunology annual scientific meeting 2015. Issue 1 (May 2016) - Côté, Marie-Ève; Boulay, Marie-Ève; Plante, Sophie; Chakir, Jamila; Boulet, Louis-Philippe; Ahmed, Hanan; Ospina, Maria-Beatriz; Sideri, Kyriaki; Vliagoftis, Harissios; Johnson, Sara; Woodgate, Roberta; Cros, Guilhem; et al.
Table of contents A1 Role of fibrocytes in allergic rhinitis Marie-Ève Côté, Marie-Ève Boulay, Sophie Plante, Jamila Chakir, Louis-Philippe Boulet A2 Patterns of aeroallergens sensitization in Northern Alberta Hanan Ahmed, Maria-Beatriz Ospina, Kyriaki Sideri, Harissios Vliagoftis A3 Addressing acceptable risk for adolescents with Food-Induced Anaphylaxis (FIA) Sara F. Johnson, Roberta L. Woodgate A4 Outcomes of matched related and unrelated bone marrow transplantation after reduced-toxicity conditioning for children suffering from Chronic Granulomatous Disease Guilhem Cros, Pierre Teira, Sonia Cellot, Henrique Bittencourt, Helene Decaluwe, Marie France Vachon, Michel Duval, Elie Haddad A5 Outcomes of patients with severe combined immunodeficiency (SCID) prior to and after initiation of newborn screening for SCID in Ontario Vy H.D. Kim, Anne Pham-Huy, Eyal Grunebaum A6 Detection of regulatory B cells in the airways of subjects with asthma John-Paul Oliveria, Stephanie Phan, Mark W. Tenn, Damian Tworek, Steven G. Smith, Adrian J. Baatjes, Caitlin D. Obminski, Caroline E. Munoz, Tara X. Scime, Roma Sehmi, Gail M Gauvreau A7 Characterization of IgE-expressing B cells in the airways and peripheral blood of allergic asthmatic subjects John-Paul Oliveria, Stephanie Phan, Mark W. Tenn, Brittany M Salter, Steven G Smith, Caitlin D Obminski, Caroline E Munoz, Abbey Schlatman, Tara X Scime, Rick Watson, Roma Sehmi, Gail M Gauvreau A8 Pregnancy: could it be a risk factor for primary immunodeficient patients Roya Sherkat, Razieh Khoshnevisan, Saba Sheikhbahaei A9 Clinical experience with Octagam: a Canadian retrospective chart review Stephen Betschel, Richard Warrington, Robert Schellenberg A10 Kounis syndrome secondary to contrast media with inferior ST elevations and bilateral ischemic stroke Michael N Fein, Jean-Philippe Pelletier A11 Honey bee venom immunotherapy ineffective in bumble bee-induced anaphylaxis: case report and review of literature Manstein Kan, Robert Schellenberg A12 Delayed immune reconstitution occurring after multiple immune complications of hematological stem cell transplantation for a leaky SCID Roxane Labrosse, Guilhem Cros, Pierre Teira, Henrique Bittencourt, Helene Decaluwe, Michel Duval, Elie Haddad A13 Comparison of Three Case Reports of Acquired Angioedema: presentation, management and outcome Raymond Mak, James Loh, Amin Kanani A14 Sitagliptin-associated angioedema not related to concurrent use of ARB or ACE inhibitor Dominik A. Nowak, Paul K. Keith A15 Sneddon-Wilkinson subcorneal pustular dermatosis associated with an IgA monoclonal gammopathy Daniel Pannozzo, Dominik A. Nowak, Hermenio C. Lima A16 Omalizumab can be effective in patients with allergic bronchopulmonary aspergillosis Diana Pham, Hoang Pham, Gonzalo G. Alvarez, Istvan T. Bencze, Krishna B. Sharma, Mark Smith, Shawn Aaron, Jennifer Block, Tara Keays, Judith Leech, David Schneidermen, Jodi Cameron, Jennifer Forgie, Alicia Ring, John W. O'Quinn, Stephanie Santucci, William H. Yang A17 Efficacious use of omalizumab in the treatment of cystic fibrosis Diana Pham, Hoang Pham, Ena Gaudet, Shawn Aaron, Stephanie Santucci, William H. Yang A18 HAE with normal C1-INH with inconsistent response to C1 esterase inhibitor infusion but reliably responsive to icatibant Hoang Pham, Stephanie Santucci, William H. Yang A19 Anaphylaxis reaction to lactase enzyme Mathew R. Voisin, Rozita Borici-Mazi A20 Risk of solid tumor malignancies in patients with primary immune deficiency Kateryna Vostretsova, Donald F. Stark A21 Is it time to adopt the chromogenic assay for measuring C1 esterase inhibitor function in patients with HAE Type 2? Elizabeth Yeboah, Paul K. Keith A22 Emergency department visits for anaphylaxis and allergic reactions Michelle Martin-Rhee, Cheryl Gula, Clare Cheng, Geoff Paltser A23 START: Susceptibility To food Allergies in a Registry of Twins Alizée Dery, Ann Clarke, Kari Nadeau, Laurie Harada, Kimberley Weatherall, Celia Greenwood, Denise Daley, Yuka Asai, Moshe Ben-Shoshan A24 Qualifying the diagnostic approach employed by allergists when managing patients with self-diagnosed non-celiac gluten sensitivity (NCGS) Lee Horgan, Teresa Pun A25 Retrospective analysis on the agreement between skin prick test and serum food specific IgE antibody in adults with suspected food allergy Ling Ling, Maria B. Ospina, Kyriaki Sideri, Harissios Vliagoftis A26 Staple food hypersensitivity from infancy to adolescence: a report from the BAMSE cohort Jennifer L.P. Protudjer, Mirja Vetander, Marianne van Hage, Ola Olén, Magnus Wickman, Anna Bergström A27 Evaluating the impact of supervised epinephrine autoinjector administration during food challenges on perceived parent confidence Timothy Teoh, Christopher Mill, Tiffany Wong, Ingrid Baerg, Angela Alexander, Kyla J. Hildebrand, John Dean, Boris Kuzeljevic, Edmond S. Chan A28 Local immunoglobulin production toAspergillus fumigatus cystic fibrosis Jonathan Argeny, Mia Gona-Hoepler, Petra Fucik, Edith Nachbaur, Saskia Gruber, Reto Crameri, Andreas Glaser, Zsolt Szépfalusi, Claudio Rhyner, Thomas Eiwegger A29 Extract consumption with skin prick test (SPT) devices Greg. Plunkett, Brad Mire A30 Evaluation of our cases with nonsteroidal anti-inflammatory drug reactions Mehtap Yazicioglu, Ceren Can, Gokce Ciplak A31 Reasons for referral and final diagnoses in a tertiary care pediatric allergy clinic Victoria E. Cook, Kyla J. Hildebrand, Elodie Portales-Casamar, Christopher Mill, Edmond S. Chan A32 Internist referral practices for inpatients with self-reported penicillin allergies at a tertiary care teaching hospital Michael N Fein, Emil P Nashi A33 Assessing the risk of reactions in children with a negative oral challenge after a subsequent use of amoxicillin Sofianne Gabrielli, Christopher Mill, Marie-Noel Primeau, Christine Lejtenyi, Elena Netchiporouk, Alizee Dery, Greg Shand, Moshe Ben-Shoshan A34 Validity of self-reported penicillin allergies Erica Hoe, Joel Liem A35 Effectiveness of allergy-test directed elimination diets in eosinophilic esophagitis Jason K. Ko, David J.T. Huang, Jorge A. Mazza A36 Allergy testing and dietary management in pediatric eosinophilic esophagitis (EoE): A retrospective review of a tertiary Canadian centre's experience Mary McHenry, Anthony Otley, Wade Watson A37 Visualizing the impact of atopic and allergic skin disease Dominik A. Nowak, John N. Kraft A38 Cystic fibrosis with and without nasal polyposis in pediatric patients: a cross-sectional comparative study Mihaela Paina, Ahmed A. Darwish Hassan, Delia Heroux, Lynn Crawford, Gail Gauvreau, Judah Denburg, Linda Pedder, Paul K. Keith A39 Evaluation of macrolide antibiotic hypersensitivity: the role of oral challenges in children Bahar Torabi, Marie-Noel Primeau, Christine Lejtenyi, Elaine Medoff, Jennifer Mill, Moshe Ben-Shoshan A40 Venom allergy testing: is a graded approach necessary? Jaclyn A. Quirt, Xia Wen, Jonathan Kim, Angel Jimenez Herrero, Harold L. Kim A41 The role of oral challenges in evaluating cephalosporin hypersensitivity reactions in children Magdalena J. Grzyb, Marie-Noël Primeau, Christine Lejtenyi, Elaine Medoff, Jennifer Mill, Moshe Ben-Shoshan A42 Breastfeeding and infant wheeze, atopy and atopic dermatitis: findings from the Canadian Healthy Infant Longitudinal Development Study Meghan B. Azad, Zihang Lu, Allan B. Becker, Padmaja Subbarao, Piushkumar J. Mandhane, Stuart E. Turvey, Malcolm R. Sears, the CHILD Study Investigators A43IL33 DNA methylation in bronchial epithelial cells is associated to asthma Anne-Marie Boucher-Lafleur, Valérie Gagné-Ouellet, Éric Jacques, Sophie Plante, Jamila Chakir, Catherine Laprise A44 NRF2 mediates the antioxidant response to organic dust-induced oxidative stress in bronchial epithelial cells Michael Chen, Toby McGovern, Mikael Adner, James G. Martin A45 The effects of perinatal distress, immune biomarkers and mother-infant interaction quality on childhood atopic dermatitis (rash) at 18 months Nela Cosic, Henry Ntanda, Gerald Giesbrecht, Anita Kozyrskyj, Nicole Letourneau A46 Examining the immunological mechanisms associated with cow's milk allergy Bassel Dawod, Jean Marshall A47 Tryptase levels in children presenting with anaphylaxis to the Montréal Children's Hospital Sarah De Schryver, Michelle Halbrich, Ann Clarke, Sebastian La Vieille, Harley Eisman, Reza Alizadehfar, Lawrence Joseph, Judy Morris, Moshe Ben-Shoshan A48 Secondhand tobacco smoke exposure in infancy and the development of food hypersensitivity from childhood to adolescence Laura Y. Feldman, Jesse D. Thacher, Inger Kull, Erik Melén, Göran Pershagen, Magnus Wickman, Jennifer L. P. Protudjer, Anna Bergström A49 Combined exposure to diesel exhaust and allergen enhances allergic inflammation in the bronchial submucosa of atopic subjects Ali Hosseini, Tillie L. Hackett, Jeremy Hirota, Kelly McNagny, Susan Wilson, Chris Carlsten A50 Comparison of skin-prick test measurements by an automated system against the manual method Saiful Huq, Rishma Chooniedass, Brenda Gerwing, Henry Huang, Diana Lefebvre, Allan Becker A51 The accurate identification and quantification of urinary biomarkers of asthma and COPD through the use of novel DIL- LC-MS/MS methods Mona M. Khamis, Hanan Awad, Kevin Allen, Darryl J. Adamko, Anas El-Aneed A52 Systemic immune pathways associated with the mechanism of Cat-Synthetic Peptide Immuno-Regulatory Epitopes, a novel immunotherapy, in whole blood of cat-allergic people Young Woong Kim, Daniel R. Gliddon, Casey P. Shannon, Amrit Singh, Pascal L. C. Hickey, Anne K. Ellis, Helen Neighbour, Mark Larche, Scott J. Tebbutt A53 Reducing the health disparities: online support for children with asthma and allergies from low-income families Erika Ladouceur, Miriam Stewart, Josh Evans, Jeff Masuda, Nicole Letourneau, Teresa To, Malcolm King A54 Epigenetic association ofPSORS1C1 and asthma in the Saguenay-Lac-Saint-Jean asthma study Miriam Larouche, Liming Liang, Catherine Laprise A55 IL-33 induces cytokine and chemokine production in human mast cells Stephanie A. Legere, Ian D. Haidl, Jean-Francois Legaré, Jean S. Marshall A56 Reference ranges for lung clearance index from infancy to adolescence for Canadian population Zihang Lu, Malcolm Sears, Theo J. Moraes, Felix Ratjen, Per Gustafsson, Wendy Lou, Padmaja Subbarao A57 Kingston Allergy Birth Cohort: cohort profile and mother/child characteristics to age 2 Michelle L. North, Elizabeth Lee, Vanessa Omana, Jenny Thiele, Jeff Brook, Anne K. Ellis A58 Cow's milk protein specific IgE, IgA and IgG4 as a predictor of outcome in oral immunotherapy Tanvir Rahman, Duncan Lejtenyi, Sarah De Schryver, Ryan Fiter, Ciriaco Piccirillo, Moshe Ben-Shoshan, Bruce Mazer A59 Age of peanut introduction and development of reactions and sensitization to peanut Elinor Simons, Allan B. Becker, Rishma Chooniedass, Kyla Hildebrand, Edmond S. Chan, Stuart Turvey, Padmaja Subbarao, Malcolm Sears A60 Multi-omic blood biomarker signatures of the late phase asthmatic response Amrit Singh, Casey P. Shannon, Young Woong Kim, Mari DeMarco, Kim-Anh Le Cao, Gail M. Gauvreau, J. Mark FitzGerald, Louis-Philippe Boulet, Paul M. O'Byrne, Scott J. Tebbutt A61 Early life gut microbial alterations in children diagnosed with asthma by three years of age Leah T. Stiemsma, Marie-Claire Arrieta, Jasmine Cheng, Pedro A. Dimitriu, Lisa Thorson, Sophie Yurist, Boris Kuzeljevic, Diana L. Lefebvre, Padmaja Subbarao, Piush Mandhane, Allan Becker, Malcolm R. Sears, Kelly M. McNagny, Tobias Kollmann, the CHILD Study Investigators, William W. Mohn, B. Brett Finlay, Stuart E. Turvey A62 The relationship between food sensitization and atopic dermatitis at age 1 year in a Canadian birth cohort Maxwell M. Tran, Diana L. Lefebvre, Chinthanie F. Ramasundarahettige, Allan B. Becker, Wei Hao Dai, Padmaja Subbarao, Piush J. Mandhane, Stuart E. Turvey, Malcolm R. Sears A63 Allergen inhalation enhances Toll-like receptor-induced thymic stromal lymphopoietin receptor expression by hematopoietic progenitor cells in mild asthmatics Damian Tworek, Delia Heroux, Seamus N. O'Byrne, Paul M. O'Byrne, Judah A. Denburg A64 The Allergic Rhinitis Clinical Investigator Collaborative – replicated eosinophilia on repeated cumulative allergen challenges in nasal lavage samples Laura Walsh, Mena Soliman, Jenny Thiele, Lisa M. Steacy, Daniel E. Adams, Anne K. Ellis A65 The CHILD Study: optimizing subject retention in pediatric longitudinal cohort research Linda Warner, Mary Ann Mauro, Robby Mamonluk, Stuart E. Turvey A66 Differential expression of C3a and C5a in allergic asthma ChenXi Yang, Amrit Singh, Casey P. Shannon, Young Woong Kim, Ed M. Conway, Scott J. Tebbutt